EVALUATING OR SELECTING A SUITABLE INFORMATION SYSTEM DEVELOPMENT METHODOLOGY: A CASE STUDY - De Vries, M.R. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: Information system development methodologies have been applied by numerous organisations since the mid-1980s in an attempt to improve the efficiency and effectiveness of designing and developing new information systems. Despite advances in methodologies, tools and techniques, productivity is still low. High quality products are seldom produced and at high cost. The advantages and disadvantages of using a methodological approach is discussed. The author identifies the key drivers for applying an information system development methodology successfully and provides a method for selecting or evaluating a methodology tailored to an organisation